Atividade antibacteriana de Óleos Essenciais sobre Streptococcus mutans e Staphylococcus aureus - Freire, I.c.m.; Pérez, A.l.a.l.; Cardoso, A.m.r.; Mariz, B.a.l.a.; Almeida, L.f.d.; Cavalcanti, Y.w. [UNESP]; Padilha, W.w.n. (Sociedade Brasileira de Plantas Medicinais, 2014)
The aim of this study is to evaluate the in vitro antimicrobial activity of essential oils of Ocimum basilicum (basil), Thymus vulgaris (thyme) and Cinnamomum cassia (Chinese cinnamon) against strains of Streptococcus mutans (ATCC 25175) and Staphylococcus aureus (ATCC 25923). The antibacterial activity of the essential oils was determined by Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC). The MIC was obtained by the microdilution technique using 96-well microplates, in which we inserted: 100µL of Brain Heart Infusion broth at double concentration, 100µL of the dilution of the essential oils and 10µL of bacterial suspension (1.5 x 10(6) organisms / mL). The products were diluted from the initial concentration of 8% up to 0.0625%. The MIC corresponded to the last dilution in which there was no presence of bacteria or turbidity in the culture medium. The MBC was obtained by seeding, in Mueller-Hinton agar, 10µL aliquots of dilutions corresponding to the MIC and the two immediately preceding ones (2MIC and 4MIC). The plates were incubated at 37°C in a bacteriological incubator for 24 hours. The tests were performed in triplicate, and 2% Chlorhexidine Digluconate was the control product. For S. aureus, the MIC and MBC of the essential oils of C. cassia, O. basilicum and T. vulgaris were 0.0625%, 0.0625% and 4%, respectively. For S. mutans, the MIC and MBC of the essential oils of C. cassia and T. vulgaris were 0.125% and 0.25%, respectively. The MIC of O. basilicum against S. mutans was 4% and the essential oil showed no bactericidal action. Chlorhexidine Digluconate presented antibacterial activity against all organisms. The evaluated essential oils presented antibacterial activity against the strains of S. mutans and S. aureus, and we highlight the essential oils from C. cassia and T. vulgaris with the lowest MIC and MBC.

Este trabalho objetivou avaliar a ação antimicrobiana in vitro dos óleos essenciais de Ocimum basilicum (Manjericão Exótico), Thymus vulgaris (Tomilho Branco), e de Cinnamomum cassia (Canela da China) sobre cepas bacterianas de Streptococcus mutans (ATCC 25175) e Staphylococcus aureus (ATCC 25923). A atividade antibacteriana dos óleos essenciais foi determinada pela Concentração Inibitória Mínima (CIM) e a Concentração Bactericida Mínima (CBM) através da técnica de microdiluição e do esgotamento. Para a CIM, foram utilizadas placas de 96 poços e inseriu-se 100µL de caldo BHI, 100µL da diluição dos óleos essenciais no primeiro poço e 10µL da suspensão bacteriana (1,5x10(6) microrganismos/mL). Realizou-se a diluição seriada partindo-se da concentração inicial de 8% até 0,0625%. A CIM correspondeu à última diluição na qual não foi verificada a presença de bactérias. Para obter a CBM, realizou-se a semeadura em Ágar Miller-Hinton das diluições correspondentes a CIM, 2CIM e 4CIM. As placas foram incubadas a 37º C em estufa bacteriológica por 24 horas. Os testes foram realizados em triplicata tendo a clorexidina como controle positivo. Para S. aureus (ATCC 25923) a CIM e CBM dos óleos essenciais de C. cassia, O. basilicum e T. vulgaris foram 0,0625%, 4% e 0,0625%, respectivamente. Para S. mutans a CIM e a CBM dos óleos essenciais de C. cassia e T. vulgaris foram 0,125% e 0,25%, respectivamente. Já a CIM do O. basilicum foi 4% e não apresentou ação bactericida. Conclui-se que os óleos essenciais avaliados apresentaram ação antibacteriana frente a cepas de S. mutans e S. aureus, sendo que os menores valores de CIM e de CBM foram provenientes dos óleos de C. cassia e T. vulgaris.
Antibacterial Activity of Essential Oils against Strains of Streptococcus and Staphylococcus
Keywords: Streptococcus mutans; Staphylococcus aureus; Microbiologia; Streptococcus mutans; Staphylococcus aureus; Microbiology; Antimicrobial agents